Characterization of tanalith E treated wood flour filled polylactic acid composites. (July 2019) - Dalu, Mohammed; Temiz, Ali; Altuntaş, Ertuğrul; Demirel, Gaye Köse; Aslan, Mustafa
Abstract: In this study, it was investigated the feasibility of wood-plastic composites (WPCs) made of polylactic acid (PLA), as a biobased thermoplastic matrix material and treated wood flour ( Pinus sylestris L.) with Tanalith E, as organic reinforcement of matrix material. The wood flour amounts in composites were 30, 40 and 50 wt% by weight fiber loadings. Maleic anhydrid grafted polyethylene (MAPE) as a coupling agent was also used to improve the compatibility between the fiber and plastic matrix. Density, void content, water absorption, thickness swelling, tensile test, flexural properties, impact strengths, thermal properties, microstructural and morphological characterization and durability against white rot ( Trametes versicolor (MAD-697) (L:Fr.) Pilat) and brown rot ( Coniophora puteana ((Schumach.: Fr.) P. Karst (Mad-15)) were used to characterize the WPCs properties. Results revealed that WPCs with untreated wood flour had higher densities compared to those of WPCs with treated wood flour for the same wood contents due to higher void content of treated wood flour-PLA composites. In addition, water absorption and thickness swelling rate of WPCs increased with an increasing the fiber content in WPCs. Regarding to mechanical properties, PLA composites with treated wood flour content of 40 wt% showed best mechanical performance among the different fiber contents. The percentage of weight loss and residual ratio increased with increases in both the wood flour content and the temperature. All tested WPCs had lower weight losses than that of control (untreated wood) samples due to encapsulation of wood by biobased thermoplastic matrix. Highlightss: Characterization of treated wood flour filled PLA composites were determined. Water absorption and thickness swelling rate of WPCs increased with an increasing the fibre content. 40 wt% with treated wood flour content showed best mechanical performance.